Exploring The Impact of Inter Professional Education on Team Dynamics and Patient Outcomes: Nursing, Radiology, Laboratory, Dental and Medical Secretary Integration - Manal Ali Nasseri (7), Mashael Ali Mohemmed Waild (8), Habshi Mohammed Asheeri (9), Soliman Abdullah Alquzi (10), Ahmed Soliman Alquzi (11), Abdulaziz Hawi Hassan Hakami (12)., Mohammed Yahyah Buhays Alkinany (1), Maher Mohammed Abdullah Alsaidan (2), Dalal Mohammed Abdullah Alsaidan (3), Reema Khalid Al Dulayqan (4), Abdullah Harrab Farea Al-Shatri (5), Sahal Ramzi Alamri (6) (Journal of Population Therapeutics and Clinical Pharmacology, 2022)
Effective interprofessional collaboration is vital for delivering high-quality patient care. However, health professions have trditionally been educated in silos, with little exposure to other disciplines during training.While research supports interprofessional education's IPE benefits, few studies have evaluated programs integrating nursing, radiology, laboratory, dental and medical secretary students. IPE is increasingly recognized as important for training a healthcare workforce capable of delivering high-quality, team-based patient-centered care.The overarching goal of IPE is to prepare a collaboration ready workforce by developing interprofessional values and education. Specific objectives include improving understanding of roles, fostering mutual respect and trust, enhancing effective communication skills and promoting team-based problem solving. IPE aims to transfer these skills and attitudes into clinical practice to benefit clients, populations and systems of care.A longitudinal mixed-methods study was conducted involving nursing (n=30), radiology (n=15), laboratory (n=10), dental (n=5) and medical secretary (n=10) students who participated in a mandatory final-year interprofessional education program between 2015-2017. The program consisted of four half-day workshops incorporating simulated patient scenarios and team-based learning activities. To address the research questions, we collected both quantitative and qualitative data. Team dynamics were measured at 6, 12, 24 and 36 months post-graduation using a validated tool incorporating Likert-scale questions on vision, participation safety, support for innovation and task orientation. Patient outcomes were assessed by retrospective chart review of 100 patients seen by each graduate in their current roles over the past year.Both quantitative and qualitative data were analyzed using descriptive statistics and thematic analysis respectively.Results showed significantly higher ratings of vision, participation safety, support for innovation and task orientation in graduate teams who had been exposed to interprofessional education compared to those without. Chart reviews found reduced length of stay and readmission rates for patients seen by interprofessional education-exposed graduates versus others. Patient satisfaction scores were also higher in this group. Our results suggest interprofessional education can positively impact subsequent team dynamics and collaboration between nursing, radiology, laboratory, dental and medical secretary graduates. Improved relationships and understanding of roles may enhance coordination and efficiency of care, leading to benefits such as reduced length of stay and readmissions. These findings are consistent with other studies demonstrating interprofessional education's influence on collaborative practice. However, our study was conducted in a single institution, and team compositions may vary in different contexts. Future research with larger, multi-site samples controlling for more factors is still needed. This review’s findings indicate that an interprofessional education program integrating nursing, radiology, laboratory, dental and medical secretary students can positively impact subsequent team dynamics and patient outcomes after graduation